Prediction equations for runoff and soil loss as influenced by different crops and slopes in lateritic soil of Konkan region, Maharashtra (India) - S.R., Kale; J.S., Dhekale; V.G., Salvi (Journal of Soil and Water Conservation, 2022)
Studies were conducted on runoffplots of 0(+ 0.5), 2.50, 5.00 and 7.50% slopes with Themada grass (Uncultivated Fallow), Ragi (Eluicine coracana) and Groundnut (Amchis hypogaea) as test crops at Konkan Krishi Vidyapeeth, Dapoli, Dint. Ratnagiri (India), during 1989 to 1991. The data on runoff and soil loss gathered through these treatments were analysed to fit regression equations giving effect of rainfall on runoff and effect of runoff on soil loss. The runoff through all the treatments was found to be highly correlated with rainfall. The coefficient of the determinant was in the range of 0.67 to 0.93. Soil loss was also highly correlated with runoff through all the treatment with coefficient of determinant in the range of 0.37 to 0.93. Runoff and soil loss was maximum through Ragi, followed by Uncultivated Fallow and Groundnut, respectively, through all treatments.